Cover Feature: Phosphorescence at Low Temperature by External Heavy‐Atom Effect in Zinc(II) Clusters (Chem. Eur. J. 23/2019). Issue 23 (25th March 2019) - Kobayashi, Fumiya; Ohtani, Ryo; Teraoka, Saki; Yoshida, Masaki; Kato, Masako; Zhang, Yingjie; Lindoy, Leonard F.; Hayami, Shinya; Nakamura, Masaaki
Abstract : Zinc(II) complexes have a significant hurdle to overcome to exhibit phosphorescence because of the absence of spin‐orbital coupling (SOC) in the Zn II ion. The present manuscript reports the phosphorescent behaviour of a Zn II cluster [Zn7 L6 (μ3 ‐OMe)2 (μ3 ‐OH)4 ]I2 (HL=methyl‐3‐methoxysalicylate) promoted by the external heavy‐atom effect (EHE) associated with the presence of iodide counter anions that act to introduce SOC into the system. This heptanuclear Zn II cluster with I − counter anions shows phosphorescence ( λ max =520 nm) with an extremely long emission lifetime ( τ =95.3 ms) at 77 K. More information can be found in the Communication by S. Hayami, M. Nakamura, et al. onpage 5875 .